Effect of concept mapping instructional strategy on senior secondary school students’ retention level in biology in Kwara State - Oyeyemi, Waheed Tunde; Olorundare, Adekunle Solomon; Bolaji, Hameed Olalekan (Assimilation: Indonesian Journal of Biology Education, 2024)
Cell Division topic in Biology is often challenging for students due to poor understanding. The study investigated how concept mapping impacts the retention of senior secondary school biology students in Kwara State, Nigeria. Using a quasi-experimental design with 77 students from two public junior high schools. The design is suitable due to its limitations, such as the inability to assign participants and the use of pre-existing groups randomly. Data was collected using Biology Concept Map Instructional Strategy for Teaching Cell Division and Biology Performing Test. The instruments were validated by experts and tested on 40 students. The results showed a significant difference in retention levels between male and female students when teaching Cell Division using this strategy (p0.05). It is recommended that Biology teachers prioritize the use of Computer-Machine Interfaces when teaching Cell Division, particularly for students with low retention and female students. The concept mapping instructional strategy significantly improves students' retention levels in Cell Division Biology, particularly among female students. It also indicates that gender is greatly influenced by this strategy, with females showing higher retention rates. Therefore, it suggests that using this approach in senior secondary school biology education can significantly enhance retention rates.